Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s0007114516003317
|View full text |Cite
|
Sign up to set email alerts
|

Diet misreporting can be corrected: confirmation of the association between energy intake and fat-free mass in adolescents

Abstract: Subjective energy intake (sEI) is often misreported, providing unreliable estimates of energy consumed. Therefore, relating sEI data to health outcomes is difficult. Recently, Börnhorst et al. compared various methods to correct sEI-based energy intake estimates. They criticised approaches that categorise participants as under-reporters, plausible reporters and over-reporters based on the sEI:total energy expenditure (TEE) ratio, and thereafter use these categories as statistical covariates or exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 60 publications
(122 reference statements)
1
31
0
Order By: Relevance
“…Similarly, Wang et al (13) found that the association between evening EI and overweight or obesity disappeared after excluding energy misreporters. However, these findings should be interpreted with caution, because evidence suggests that the exclusion of energy misreporters may introduce selection bias (62). Indeed, post hoc analysis of our data found that energymisreporting status was significantly associated with weight status (x 2 = 32.22, P = 0.0002) and 29% of overweight or women compared with 17% of healthy-weight women were classified as energy underreporters.…”
mentioning
confidence: 59%
“…Similarly, Wang et al (13) found that the association between evening EI and overweight or obesity disappeared after excluding energy misreporters. However, these findings should be interpreted with caution, because evidence suggests that the exclusion of energy misreporters may introduce selection bias (62). Indeed, post hoc analysis of our data found that energymisreporting status was significantly associated with weight status (x 2 = 32.22, P = 0.0002) and 29% of overweight or women compared with 17% of healthy-weight women were classified as energy underreporters.…”
mentioning
confidence: 59%
“…These data were not available to us due to the design of the questionnaires used in the study. However, because subjective energy intake is often misreported, adjustment for external predictors such as BMI and physical activity could be a better method than energy intake estimated from FFQs or another subjective dietary assessment method [24,25]. Lastly, we used a self-constructed questionnaire to assess dietary restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…One can then statistically determine whether an individual is likely to be under‐reporting by comparing their energy intake as a multiple of their BMR (Goldberg method); or as a multiple of their estimated energy requirement (EER) . Once these individuals are identified, the bias due to under‐reporting can be addressed by excluding these implausible reporters, although exclusion may lead to selection bias; or by the use of statistical techniques that adjust for total caloric intake, dietary composition, or the energy density of nutrients, for example, by including these variables or predictors of them as control variables in the regression model …”
Section: Introductionmentioning
confidence: 99%